Analysis Of Discourse Markers Used In Jay Shetty's On Purpose Program - Rahmah, Safinatun Najatir; Elisa Nurul Laili (Politeknik Kampar, 2023)
In communicating, we often experience misunderstandings about something being discussed, or get stuck in awkward situations because the conversation is not going smoothly. Discourse markers are crucial in communication, helping speakers formulate new ideas and make their speech more natural. This study analyzed the types and functions of discourse markers in Jay Shetty’s On Purpose program using a descriptive-qualitative approach. The researcher combined the theories of Biber et al. (1999) and Castro (2009) to classify the types and functions of discourse markers. The result revealed that the most commonly used discourse marker is the clause “you know”, and the dominant function of discourse markers that are used is response or reaction markers and back-channel signals, which help speaker express reaction to previous discourse, show understanding, and continued attention while other speakers are getting their turn.